How Competence of Production, Attention, Retention, Motivation, and Innovation can Improve Students’ Scientific Writing Skills - Indrya Mulyaningsih; Wahyudi Rahmat; Djohar Maknun; Winci Firdaus (International Journal of Language Education, 2022)
This research aimed to prove the role of production, attention, retention, motivation, and innovation in students’ scientific writing skills at the Islamic Study College (PTAI) in Cirebon. This experimental research used a quasi-experimental design and a nonequivalent control group design. The experiment was conducted in two groups, experiment and control groups. The research samples included Lecturers from a public Islamic University. The experiment group samples were 38 students of the Philosophy of Religion Department. The control group consisted of 33 Islamic Guidance and Counseling Department students. The collection technique used was tested, comprised of a pretest and posttest. The two groups were given the same tests (pretest and posttest), and the results were compared. The instrument used in this research was a test. Validity determination for the scientific writing ability variable was not measured statistically but through construct validity. The reliability test resulted in a reliability coefficient from an assessor of 0.82, while all assessors' average rating reliability coefficient was 0.93. The normality test results on scientific writing ability data with the control class show Lo = 0.106 < Lt = 0.154. Meanwhile, the normality test on the experiment class’s scientific writing ability data results in a maximum Lo of 0.106 and Lt = 0.144. The balance test results show the score of tcount = 1.51 < ttable = 1.67. The data analysis with t independent test resulted in the score of tcount > ttable (10.45 > 1.65). This shows that the competence of production, attention, retention, motivation, and innovation can improve students’ scientific writing skills.